Surgical and clinical management of a patient with Glanzmann thrombasthenia: A case report - Gomes, Mônica Fernandes [UNESP]; De Melo, Renata Marques [UNESP]; Plens, Glauco; Pontes, Elitânia Marinho; Silva, Marcelo Milone; Da Rocha, João Carlos [UNESP] (My University, 2004)
A 6-year-old girl with Glanzmann thrombasthenia presented with caries and periapical lesions in the primary mandibular second molars and moderate gingivitis of the maxillary and mandibular anterior teeth. Dental extraction was recommended, and before every surgical intervention, the patient underwent platelet-concentrate transfusion to prevent hemorrhage. Epsilon aminocaproic acid was administered 6 hours before, and 48 hours after every dental procedure to prevent bleeding. In this case, treatment was effective in the prevention of hemorrhagic complications, during the required dental procedures.
Keywords: Clinical management; Dental extraction; Glanzmann thrombasthenia; IIb/IIIa glycoprotein complex; Odontologic management; fibrinogen receptor; thrombocyte concentrate; blood transfusion; case report; clinical examination; clinical feature; dental surgery; disease severity; female; gingivitis; Glanzmann disease; human; management; mandible; molar tooth; oral bleeding; preschool child; tooth extraction; tooth periapical disease; treatment indication; treatment outcome; Aminocaproic Acids; Child; Dental Care for Chronically Ill; Dental Caries; Female; Humans; Oral Hemorrhage; Periapical Periodontitis; Thrombasthenia; Tooth Extraction; Vasoconstrictor Agents